Identification and evaluation of apoptotic compounds from Garcinia Oligantha - Han, Quan-Bin (2013)
Four new compounds, oliganthins A–D (1–4), and one known caged xanthone gaudichaudione H (5) were isolated from the stems of Garcinia oligantha. The structures of the new compounds were elucidated by spectroscopic evidences. All of the five compounds were evaluated for their apoptosis-inducing effects using HeLa-C3 cells which have been genetically engineered to produce a fluorescent biosensor capable of detecting caspase-3 activation. All of them induced cell apoptosis at 10 μM or lower concentrations. The apoptotic activity of oliganthins A, B and gaudichaudione H were further confirmed by detecting the cleavage of PARP, which is the substrate of activated caspase-3, in these compounds-treated cells using the method of Western blot. Moreover, the values of IC50 were measured for all five compounds on HeLa cells using the MTT assay. Among them, gaudichaudione H had the lowest IC50 value of 0.90 μM, while the other four new compounds had IC50 values of 1.58, 1.52, 4.15, and 7.82 μM, respectively. These results show that gaudichaudione H has the strongest apoptosis-inducing effect and cell growth inhibition effect among these xanthones and it may have the potential to be developed into a new anticancer agent.